Water‐Assisted Liftoff of Polycrystalline CdS/CdTe Thin Films Using Heterogeneous Interfacial Engineering. Issue 14 (27th May 2019) - Magginetti, David J.; Aguiar, Jeffery A.; Winger, Joshua R.; Scarpulla, Michael A.; Pourshaban, Erfan; Yoon, Heayoung P.
Abstract: Recent advances in device design and process optimizations have enabled the production of CdTe devices on flexible substrates, but the necessary high‐temperature processing (>450 °C) to recrystallize grains limits the use of alternative lightweight substrates. Here, a new synthesis method is reported to create a freestanding CdS/CdTe film by combining high‐temperature depositions (CdS/CdTe on Si/SiO2 ) and a simple lift‐off process in a water environment at room temperature. Analysis of the results indicate that the delamination is facilitated by the innate lattice mismatch as well as the presence of an unexpected Te‐rich layer (≈20 nm), which accumulates on the SiO2 surface. High‐resolution electron microscopy and spectroscopy measurements confirm that the CdS/CdTe film is physically liberated from the substrate without leaving any residue, while also preserving their initial structural and compositional properties. Abstract : A new synthesis method allows the high‐temperature processing for grain growth of CdS/CdTe, while enabling simple liftoff in water at room temperature. This interfacial delamination is facilitated by stress‐induced deformation and strain‐facilitated chemical debonding in a presence of Te‐rich layer at the CdS/SiO2 interface. Freestanding CdS/CdTe thin films can be integrated onto low‐cost flexible substrates that have a limited temperature tolerance.